How the bending mechanics of setae modulate hydrodynamic sensing in copepods - Shen, Xinhui (2020)
Copepods sense the hydrodynamic disturbances induced by swimming planktonic prey, potential mates, and predators through the bending of setae on their first antennae and other appendages. While the flows induced by these sources have been studied and are crucial for the mechanoreception of copepods, there is little knowledge on how these flows cause the deformation of the copepod's mechanoreceptional seta. In this article, we present a mechanical model to address how the mechanics of setal deformation by hydrodynamic signals determines the sensing capabilities of copepods. We represent a generic flow around a copepod as a combination of a uniform plus shear flow, and demonstrate that the detailed geometry of the first antenna has non‐negligible effects on the flow profile across the seta. We then proceed to evaluate the setal deformations induced by such a flow oscillating at frequencies relevant for copepod sensing, and find that lower frequency signals lead to larger setal bending and are more easily detected. We investigate the effects of setal length, signal amplitude, and signal frequency on setal bending. Finally, we investigate the response time of setal bending to hydrodynamic signals, and find short response time consistent with the rapid behavioral and neurological response of copepods.